Neural Dynamics of Karaoke-Like Voice Imitation in Singing Performance - Frühholz, Sascha; Trost, Wiebke; Constantinescu, Irina; Grandjean, Didier (Frontiers in Human Neuroscience, 2020)
Beyond normal and non-imitative singing, the imitation of the timbre of another singer's voice, such as in Karaoke singing, involves the demanding reproduction of voice quality features and strongly depends on singing experience and practice. We show that precise voice imitation in a highly proficient and experienced vocal imitator, even in the absence of external auditory voice feedback, largely drew on internal cortico-subcortical auditory resources to control voicing errors based on imagined voice performance. Compared to the experienced vocal imitator, singers of a control group without experience in voice imitation used only sensorimotor feedback and demanding monitoring resources for imitation in the absence of voice feedback, a neural strategy that led, however, to a significantly poorer vocal performance. Thus, only long-term vocal imitation experience allows for the additional use of internal auditory brain resources, which result from training-induced brain plasticity, and which enable accurate vocal performance even under difficult performance conditions.